Music and Musicology in the Light of Intermediality and Intermedial Studies - Arvidson, Mats (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2012)
In this article I show how the aesthetic disciplines, to which musicology belongs, have suffered from a crisis of creativity for the past decade or so. By crisis of creativity I mean the development of new theories, which can contribute to new knowledge about music, from both historical and contemporary perspectives. With help from theories that normally lie outside of the institutional discourse of musicology, I argue that what is known as an intermedial perspective can contribute to a new understanding of music. The aim with this article is thus to introduce the concept of intermediality and the discipline of intermedial studies into the discussion of musicology as a discipline. Two parallel strands are followed, and thereby four questions are raised. The two strands are: 1) the “interarts” strand, and 2) the “Cultural Studies/media studies” strand. The four questions are: 1) What characterises the intermedial perspective? 2) Which theories appear? 3) What are the similarities and differences between the “interarts” and “Cultural Studies/media studies” strands? and finally, 4) Is there a place for a “new” humanities discipline now and in the future? Question number four deals with the premise that society today is characterised by an intensive media culture, in which all cultural expressions are woven into one another, i.e. a multimodal and intermedial culture. If we accept this premise, then for an intended humanities discipline to understand this culture, a specific, clearly formulated body of theory is needed. There appears to be an increasing demand for such a body of theory within different disciplinary fields that already has been formulated within the field of intermedial studies. My suggestion is that intermedial studies can function as a supplement to the other aesthetic disciplines.